Comparison of the Implementation of the Principle of Dominus Litis in Indonesia, Usa, and Macau - Tresna D, Lalu Panca; Anugerah, Ayang Afira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In various countries, prosecutors are central figures in the administration of criminal justice because they have the authority to determine cases (dominus litis) to be forwarded to court. Comparative study of the application of the dominus litis principle in Indonesia with other countries. Normative legal research with a Statutory and comparative approach. The application of the Dominus Litis Principle in the Criminal Procedure Code is contained in Article 1 Number (6) letters a and b; 139, as well as the principle of functional differentiation in Articles 14 and 137, based on the position and function of prosecutors in the criminal justice system regulated in Article 140 paragraph (2); Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004. Prosecutors in Indonesia are in the Executive Institution, Investigative Authority is limited to special crimes; The scope of criminal, civil and administrative prosecution is in the hands of the State and is not dual in nature, namely the Prosecutor and Macau are in the hands of the Judiciary, authorized to conduct investigations, criminal and civil prosecutions which are dual in nature, namely the Prosecutor and the United States are in the hands of the Department of Justice, have investigative authority, prosecution arrangements in the form of Federal and state prosecutions